Inklusi sosial berbasis masjid, studi perspektif penerima manfaat program warung makan gratis di masjid pemuda konsulat surabaya - Qulub, Firman Achsanul; Saleh, Isa; Gunawan, Reka; Taufikkurrohman, Diki; Ifansyah, M. Syukur; Ibrahim, Muh. Syahril Sidiq (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
Mosques not only serve as places of worship but also hold great potential as centers of inclusive social services. However, many mosques have yet to accommodate the diverse social needs of the community fully. This study aims to examine the implementation of the three dimensions of social inclusion access, participation, and empowermentin the Free Meal Program (Warung Makan Gratis). This research employs a descriptive qualitative approach with a case study method, collecting data through observation, in-depth interviews, and documentation. The findings reveal that the access dimension is reflected in open information and physical ease of reaching the program. The participation dimension is shown through the active involvement of beneficiaries in the implementation and development of the program. Meanwhile, the empowerment dimension is manifested in the positive transformation experienced by beneficiaries in social, economic, and spiritual aspects. This study concludes that the Free Meal Program represents a concrete example of mosque-based social inclusion practices that successfully reach vulnerable groups. These findings contribute to the development of literature on social inclusion in religious contexts and offer a replicable model of good practice for other mosques or religious institutions